Pendidikan dan Independensi Perempuan - Khayati, Eny Zuhni (Sunan Kalijaga State Islamic University & The Asia Foundation, 2008)
Educational right is the right for everyone in the world. There, therefore, should be no reason to discriminate against women in terms of education in Indonesia. This article discusses the importance of education and independence of women, particularly the economic independence in the family. Knowledgeable and economically strong woman will have strong self independence and be more successful in playing her role and function in both the family and society.